At the Crossroads of Survival and Death: The Reactive Oxygen Species–Ethylene–Sugar Triad and the Unfolded Protein Response. (April 2021) - Depaepe, Thomas; Hendrix, Sophie; Janse van Rensburg, Henry C.; Van den Ende, Wim; Cuypers, Ann; Van Der Straeten, Dominique
Abstract : Upon stress, a trade-off between plant growth and defense responses defines the capacity for survival. Stress can result in accumulation of misfolded proteins in the endoplasmic reticulum (ER) and other organelles. To cope with these proteotoxic effects, plants rely on the unfolded protein response (UPR). The involvement of reactive oxygen species (ROS), ethylene (ETH), and sugars, as well as their crosstalk, in general stress responses is well established, yet their role in UPR deserves further scrutiny. Here, a synopsis of current evidence for ROS–ETH–sugar crosstalk in UPR is discussed. We propose that this triad acts as a major signaling hub at the crossroads of survival and death, integrating information from ER, chloroplasts, and mitochondria, thereby facilitating a coordinated stress response. Highlights: Proteotoxic stress, or the accumulation of unfolded or misfolded proteins, occurs in response to a multitude of (a)biotic stresses and in multiple subcellular compartments, including the ER, chloroplasts, and mitochondria. The unfolded protein response or UPR is an evolutionary conserved mechanism in eukaryotes to cope with ER stress. In plants, the basic machinery for this response has been elucidated recently, but the molecular players involved in UPR, originating in other organelles, deserve scrutiny. Reactive oxygen species (ROS), ethylene (ETH), and sugars, are crucial players in stress responses. Upon proteotoxic stress, they act both up- and downstream of UPR.